Hubungan Tingkat Pengetahuan Dengan Upaya Pencegahan Diabetes Pada Remaja Awal - Niken Ayu Pratiwi; Syeptri Agiani Putri; Masrina Munawarah Tampubolon (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: The prevalence of type 2 diabetes mellitus among early adolescents has shown an increasing global trend, including in Indonesia. This condition is closely associated with unhealthy lifestyle changes and a lack of awareness regarding preventive efforts. A low level of knowledge has been identified as one of the barriers to developing effective preventive behaviors. Objective: This study aimed to determine the relationship between the level of knowledge and diabetes prevention efforts among early adolescents. Methods: A quantitative approach with a cross-sectional design was employed, involving 376 respondents from three junior high schools in Pekanbaru City, selected through proportional purposive sampling. Bivariate analysis was performed using the chi-square test, Results: The majority of respondents demonstrated a moderate level of knowledge (56.6%) and a moderate level of preventive efforts (50.3%). The chi-square test results indicated a significant relationship between knowledge level and type 2 diabetes prevention efforts (p-value = 0.000). Conclusion: These findings suggest a significant association between adolescents' knowledge levels and their efforts to prevent type 2 diabetes.